Evaluation of predictive factors of renal function recovery in renal failure secondary to urinary tract obstruction - Kalwar, Sara Rasheed; Mahar, Naveed; Lal, Murli; Memon, Mohsin Mustafa; Qureshi, Harris Hassan; Hussain, Manzoor (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the factors associated with renal function recovery in individuals with kidney failure due to obstruction in the urinary tract. Method: The prospective, descriptive study was conducted July 2020 to August 2021 at the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi, and comprised adult patients of either gender who had renal failure secondary to obstructive urinary tract. Baseline data regarding patients’ variables, including age, gender, duration of symptoms (25 days or 25 days), haemoglobin (9.85g/dl or 9.85g/dl), serum creatinine and renal cortical thickness (16.5mm or 16.5 mm), was noted on a proforma. The variables were stratified to assess impact on renal recovery. Data was analysed using SPSS 23. Results: Of the 126 patients, 43(34.13%) were males and 83(65.87%) were females. The overall mean age was 44.13±14.18 years. Renal recovery occurred in 67(78.8%) patients having duration of symptoms 25 days, and in 13(31.7%) patients with duration of symptoms 25 days (p 0.001). Renal recovery occurred in 41(58.6%) patients having haemoglobin 9.85g/dL and in 39(69.6%) patients having haemoglobin 9.85g/dL (p=0.2). Renal recovery occurred in 26(37.7%) patients with parenchymal thickness 16.5mm and in 54(94.7%) patients with renal cortical thickness 16.5mm (p 0.001). Conclusion: Symptom duration 25 days, and renal parenchymal thickness 16.5mm were found to be predictive factors of good recovery in renal failure cases secondary to obstructive uropathy. Key Words: Urinary obstruction, Obstructive nephropathy, Percutaneous nephrostomy, Renal failure.